Reviving vacuum-dried encapsulated ram spermatozoa via ICSI after 2 years of storage - Palazzese, Luca; Turri, Federica; Anzalone, Debora Agata; Saragusty, Joseph; Bonnet, Jacques; Colotte, Marthe; Tuffet, Sophie; Pizzi, Flavia; Luciani, Alessia; Matsukawa, Kazutsugu; Czernik, Marta; Loi, Pasqualino (Frontiers in Veterinary Science, 2023)
Freeze-drying techniques give alternative preservation mammalian spermatozoa without liquid nitrogen. However, most of the work has been conducted in the laboratory mouse, while little information has been gathered on large animals that could also benefit from this kind of storage. This work adapted a technique known as vacuum-drying encapsulation (VDE), originally developed for nucleic acid conservation in anhydrous state, to ram spermatozoa, and compared it to canonical lyophilization (FD), testing tong-term storage at room temperature (RT) and 4ºC. The results demonstrated better structural stability, namely lipid composition and DNA integrity, in VDE spermatozoa than FD ones, with outcomes at RT storage comparable to 4°C. Likewise, in VDE the embryonic development was higher than in FD samples (12.8% vs 8.7%, P<0.001, respectively). Our findings indicated that in large mammals, it is important to consider dehydration-related changes in 2 sperm polyunsaturated fatty acids coupled with DNA alterations, given their crucial role in embryonic development.